2009
DOI: 10.1128/jvi.00870-09
|View full text |Cite
|
Sign up to set email alerts
|

Liver Sinusoidal Endothelial Cells Are a Site of Murine Cytomegalovirus Latency and Reactivation

Abstract: In human cytomegalovirus (hCMV) infection, hematopoietic progenitor cells of the myeloid differentiation lineage are a recognized cellular site of virus latency (for more-recent reviews, see references 75 and 94), and cell differentiationdependent as well as cytokine-mediated viral gene desilencing by chromatin remodeling is discussed as the triggering event leading to virus reactivation (for a review, see reference 7). Although hematopoietic stem cell or bone marrow transplantation (BMT) is frequently associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 108 publications
4
105
0
Order By: Relevance
“…In addition, EC have recently been identified as sites of virus latency (65), and at least liver EC are able to directly stimulate a cytotoxic T-cell response (36). Using MCMV-⌬M94 constructs for conditional gene expression, we noticed substantial differences in the abilities of EC and Hc to activate a CD8 ϩ T-cell response.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, EC have recently been identified as sites of virus latency (65), and at least liver EC are able to directly stimulate a cytotoxic T-cell response (36). Using MCMV-⌬M94 constructs for conditional gene expression, we noticed substantial differences in the abilities of EC and Hc to activate a CD8 ϩ T-cell response.…”
Section: Discussionmentioning
confidence: 93%
“…It has been proposed that intermittent low-level antigen expression during latent MCMV infection induces inflationary CD8 T-cell responses (Seckert et al, 2012), and it has been reported recently that inflationary responses occur due to the proliferation of T-cells in contact with the blood circulation, rather than in organ parenchyma (Smith et al, 2014), probably because endothelial cells lining blood vessels are a major site of MCMV latency (Seckert et al, 2009). If this model is accurate, and considering that mice infected by the i.n.…”
Section: Discussionmentioning
confidence: 99%
“…MCMV latency in the mouse model of infection is clearly documented in LSEC (20), and IFN-␤ contains lytic MCMV gene expression in this cell type (21). In contrast, latent HCMV has been described in precursor cells of the myeloid lineage (14), and their ex vivo differentiation into mature mDC results in chromatin remodeling and initiation of lytic gene expression (55).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the establishment of latency appears to be restricted to certain cell types. Latent HCMV was found in blood monocytes and in progenitor cells of the myeloid lineage (14)(15)(16)(17)(18)(19), whereas liver sinusoidal endothelial cells (LSEC) were shown to be a site of MCMV latency and reactivation (20,21), although myeloid cells might also present a latent reservoir in the mouse (22,23).…”
mentioning
confidence: 99%